PENDAMPINGAN DALAM PENYUSUNAN PROGRAM PENDIDIKAN SYANTIK (SAYA ANAK ANTI KORUPSI) DI SD INPRES MUHAMMADIYAH MERAUKE - Marlyn Jane Alputila; Mulyadi Alrianto Tajuddin (Musamus University, 2022)
The purpose of the community service activity program is a program which equips teachers in providing understanding to students to have my anti-corruption child character by instilling anti-corruption values in students. The targets of PKM activities are: an increase in the knowledge of SD Muhammadiyah Merauke teachers in implementing anti-corruption programs based on learning media for students regarding anti-corruption values. The output of this activity: (1) Journal, (2) Anti-Corruption Education Module. The methodology used by the Mentoring Program is implemented through seminars, workshops and guidance in the preparation of my anti-corruption program. This includes the development of Lecture Training materials from resource persons, group discussions and brainstorming. This mentoring activity is carried out in three stages, the first stage: for outreach, the second stage: the workshop and technical guidance for module preparation, and the third stage for evaluation of assistance in the preparation of learning media according to my anti-corruption program. assistance in making anti-corruption education teaching materials where the team and resource persons who were taken from the Elementary School Teacher Education Expert Team provided understanding to participants, in this case the teachers of SD Muhammadiyah Merauke on how to implement anti-corruption values in the process of teaching and learning activities with teams and experts providing understanding through the module